An L319F mutation in transmembrane region 3 (TM3) selectively reduces sensitivity to okaramine B of the Bombyx moril-glutamate-gated chloride channel. Issue 10 (3rd October 2017) - Furutani, Shogo; Okuhara, Daiki; Hashimoto, Anju; Ihara, Makoto; Kai, Kenji; Hayashi, Hideo; Sattelle, David B.; Matsuda, Kazuhiko
Abstract : Okaramines produced by Penicillium simplicissimum AK-40 activatel -glutamate-gated chloride channels (GluCls) and thus paralyze insects. However, the okaramine binding site on insect GluCls is poorly understood. Sequence alignment shows that the equivalent of residue Leucine319 of the okaramine B sensitive Bombyx mori ( B. mori ) GluCl is a phenylalanine in the okaramine B insensitive B. mori γ-aminobutyric acid-gated chloride channel of the same species. This residue is located in the third transmembrane (TM3) region, a location which in a nematode GluCl is close to the ivermectin binding site. The B. mori GluCl containing the L319F mutation retained its sensitivity tol -glutamate, but responses to ivermectin were reduced and those to okaramine B were completely blocked. Abstract : An L319F mutation in TM3 reduces okaramine B sensitivity more profoundly than ivermectin sensitivity of Bombyx moril -glutamate-gated chloride channel. The Graphical image was illustrated using PyMOL software: